4D-DIA-Based Quantitative Proteomic Analysis Reveals the Involvement of TRPV2 Protein in Duck Tembusu Virus Replication - Jimin Chen; Fan Yang; Lianjie Lai; Huihuang Li; Chengfu Pan; Xinguo Bao; Weimin Lin; Ruiyi Lin (Viruses)
Duck Tembusu virus (DTMUV), a novel positive-sense RNA virus, has caused significant economic losses in the poultry industry of Eastern and Southeast Asia since its outbreak in 2010. Furthermore, the rapid transmission and potential zoonotic nature of DTMUV pose a threat to public health safety. In this study, a 4D-DIA quantitative proteomics approach was employed to identify differentially expressed cellular proteins in DTMUV-infected DF-1 cells, which are routinely used for virus isolation and identification for DTMUV, as well as the development of vaccines against other poultry viruses. One hundred fifty-seven differentially expressed cellular proteins were identified, including 84 upregulated and 73 downregulated proteins at 48 h post-infection, among which CXCL8, DDX3X, and TRPV2 may play crucial roles in viral propagation. Notably, for the upregulated protein TRPV2, the DTMUV replication was inhibited in TRPV2-low-expressing DF-1 cells. In summary, our research represents the application of 4D-DIA quantitative proteomics to analyze the proteomic landscape of DTMUV-infected poultry cells. These findings may provide valuable insights into understanding the interaction mechanism between DTMUV and poultry cells, as well as the identification of disease-resistant host factors in poultry breeding research.